Perbedaan Tingkat Konsumsi Energi, Aktifitas Fisik Dan Pengeluaran Uang Jajan Pada Anak Sekolah Dasar Overweight Dan Non Overweight Di ilayah Puskesmas Banjarejo, Kecamatan Taman Kota Madiun - Wiraida, Erfita Anasha, Endang Nur W, S.St., M.Si.Med, Dyah Widowati, SKM (2014)
Background : Burdern nutritional problems and begin to occur in school-aged children. The prevalence of elementary school children who are experiencing overweight by 2013 showed that amount to 7.02% and 11.2% with undernutrition. While the prevalence of overweight in primary school in Puskesmas Banjarejo reached 34.2%. High levels of energy consumption and low physical activity is a thing that can affect a person's nutritional state. Aim : This research was to analyze about the difference of energy consumption level, physical activity and pocket money for snack between overweight and non overweight chlidren. Methods of research: The design of this study was cross-sectional. Total sample 37 people in each student with Overweight and Non Overweight. Data included energy consumption level, physical activity and pocket money for snack that was collected using a questionnaires for 3x24 hours. Data were analyzed using Independent t-Test and Mann Whitney. Result : As much as (51.4 %), overweight students experienced a deficit rate of consumption. Non overweight (67.6%) with deficits and levels of consumption. Physical activity in children overweight (86.5%) with a mild. Non overweight (62.2%) with a mild activity. Students are overweight and non overweight with spending above the 50% allowance allowance total (75.6 %) Conclusion : The result of the statistic showed that variable significant difference are energy consumption level (p=0.010) and physical activity (p=0.009) between Overweight dan non Overweight children. However there was no difference in the spending allowance for snack (p= 0.335). with average daily spending of Rp 5.500,-